2017
DOI: 10.1016/j.jpeds.2017.06.073
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver-Reported Quality of Life in Youth with Down Syndrome

Abstract: Objectives To describe caregiver-reported QOL in youth with DS and to examine the role of obesity on QOL. Study design Caregivers of youth with and without DS aged 10 through 20 years completed questionnaires examining QOL (PedsQL) and weight-related QOL (Impact of Weight on Quality of Life-Kids: IWQOL-Kids). Age- and sex-specific Z-scores were generated for body mass index (BMI). Obesity was defined as a BMI≥95th percentile for age and sex. Results Caregiver-reported Total QOL, Physical Health, and Psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 37 publications
2
30
0
13
Order By: Relevance
“…To date there have only been two studies, both published very recently, examining QOL in Down syndrome in young people of a similar age range to ours [ 36 , 37 ]. Using Kidscreen-27, the earlier of the two compared individual domain scores with European normative data for the younger (12–18 year olds) component of their population while the second US study primarily involved a secondary analysis of PedsQL data collected in a study of body composition and metabolic risk in youth with Down syndrome [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date there have only been two studies, both published very recently, examining QOL in Down syndrome in young people of a similar age range to ours [ 36 , 37 ]. Using Kidscreen-27, the earlier of the two compared individual domain scores with European normative data for the younger (12–18 year olds) component of their population while the second US study primarily involved a secondary analysis of PedsQL data collected in a study of body composition and metabolic risk in youth with Down syndrome [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date there have only been two studies, both published very recently, examining QOL in Down syndrome in young people of a similar age range to ours [ 36 , 37 ]. Using Kidscreen-27, the earlier of the two compared individual domain scores with European normative data for the younger (12–18 year olds) component of their population while the second US study primarily involved a secondary analysis of PedsQL data collected in a study of body composition and metabolic risk in youth with Down syndrome [ 37 ]. In the European study the results for the young adult (aged 18–30 years) component of the population, were extremely consistent with our own findings, with lowest scores in the domains of physical wellbeing and social support while those for psychological wellbeing and school (possibly more appropriately categorised as work) environment were similar to population norms and those for autonomy and parent relations slightly higher.…”
Section: Discussionmentioning
confidence: 99%
“…Given the aforementioned characteristics and support needs specific to people with DS, it is critical to better understand and measure QoL in this population. Most studies have focused on family QoL (Marchal, Maurice-Stam, van Trotsenburg, & Grootenhuis, 2016;Vadakedom et al, 2017) or health-related QoL (Graves et al, 2016) and found significantly poorer scores for youth with DS in comparison with normative data (Haddad, Bourke, Wong, & Leonard, 2018;Jung, Chung, & Lee, 2017;Rofail et al, 2017;Shields et al, 2018;Xanthopoulos et al, 2017). Yet individual QoL is a broader and more comprehensive construct that is not merely reduced to health-related wellness as other important domains and indicators that are relevant for children with DS need to be articulated in order to develop comprehensive interventions (Murphy et al, 2017;Newton, 2018).…”
mentioning
confidence: 99%
“…A study about the quality of life of youth with DS (Xanthopoulos et al, 2017) exerted that caregivers reported a lower quality of life in youth with DS compared with youth without DS with the exception of emotional functioning. Obesity influences most domains of weight-related quality of life in youth with and without DS; therefore, providers should address weight concerns in youth with obesity even in the presence of DS.…”
Section: Introductionmentioning
confidence: 99%